Embodying Black Religions in Africa and Its Diasporas - Covington-Ward, Yolanda (Religious Cultures of African and African Diaspora People, 2021)
"Embodying Black Religions in African and Its Diasporas critically examines the role of the body as religiously motivated social action for people of African descent across the geographic regions of the African continent, the Caribbean and Latin America, the American South, and Europe. Tackling a variety of religious contexts, from Pentecostalism, to Ifa divination, to Islam, the contributors investigate the complex intersections between the body, religious expression, and the construction and negotiation of particular social relationships and collective identities"--